Physiological and Biochemical Parameters of Field Bean (Vicia faba var. minor) Seeds Stored for 33 Years - Dariusz J. Michalczyk; Magdalena Krupka; Jan Kamiński; Marta Wierzbicka; Sonia Floryańska; Wiktor Kopeć; Agnieszka I. Piotrowicz-Cieślak (Agriculture, 2023)
Changes occurring in seeds of two field bean cultivars during long-term storage at −14 °C, +4 °C and +20 °C were examined. It was found that after 33 years of storage at low temperatures, the seeds showed a significant decline in biological quality, and the seeds stored at +20 °C completely lost their germination capacity. As the seeds aged, changes in their phenolic composition, concentrations of polyamines and activity of enzymes associated with redox homeostasis and phenolic metabolism could be easily observed. The activity of ascorbate peroxidase and phenylalanine ammonia-lyase in deteriorated seeds was higher than in high-quality seeds. The activity of guaiacol peroxidase, catalase and glutathione reductase in low-quality seeds was decreased. With superoxide dismutase, the pattern was less clear-cut and depended on both seed biological quality and cultivar. Whole seed levels of spermine and spermidine decreased in ageing seeds and were lowest in non-germinating seeds. However, the opposite pattern was observed regarding spermine and spermidine, as well as putrescine, in seed coats. The obtained results indicate that changes in the activity of redox and protective systems in seeds have a clear relationship with the seed biological quality and can be detected even at a moderate level of seed deterioration. The analyses of such changes can significantly facilitate the assessment of seed quality and can therefore be of interest for seed companies and seed banks.